Peningkatan Kesejahteraan Masyarakat Melalui Konversi Lahan Pertanian ke Kelapa Sawit - Zainal Fadri; Mitria Candra; Tegu Chaniago (IAIN Batusangkar, 2021)
This study aims to explore information on improving community welfare after converting agricultural land to oil palm land. Many of the villagers carry out land conversion to increase income as a means of fulfilling their daily needs, although in reality not all of them get welfare. The method used in this research is descriptive qualitative. Data mining was carried out by interview and documentation. Interviews were conducted with smallholders who converted land to oil palm, stakeholders and local government. The results of the interview were then triangulated with documentation obtained from library searches in the form of books, articles and previous research. The results of this study indicate an increase in the welfare of the community after land conversion but with very binding rules both from the state and from the prevailing market rules.